The Fast Track Refugee Assessment Process and the Mental Health of Vulnerable Asylum Seekers. Issue 1 (2nd January 2016) - Kenny, Mary Anne; Procter, Nicholas
Abstract : On 5 December 2014, the Australian Senate passed the Maritime Powers Legislation Amendment (Resolving the Asylum Legacy Caseload) Bill 2014 (Cth). This article discusses the intersections between an aspect of the new law – the 'fast track assessment' Refugee Status Determination (RSD) procedure, mental ill health and vulnerability of asylum seekers. Insecure visa status, post-arrival stressors and living in constant uncertainty and fear of rejection and repatriation are known to compound existing pre-migration trauma for asylum seekers. The 'fast track assessment' procedure, in which a large number of asylum seekers' claims for protection will be processed under the new law, suggests a likely worsening of mental distress, despair and deterioration. The combined nature of mental health and legal support are an increasing feature of a co-ordinated and much needed integrated response to assist vulnerable asylum seekers living in the community. It is suggested that asylum seekers with an existing mental health condition who receive negative outcomes during the RSD process are particularly vulnerable. All asylum seekers should have mental health support made available to them when visa decisions are handed down or shortly afterwards.